Analysis of Entrepreneurial Readiness in Tidar University Students - Khairul Ikhwan; Warcito Warcito; Hanung Eka Atmaja (Jurnal REKOMEN (Riset Ekonomi Manajemen), 2020)
Universities as higher education institutions have an important role in the process of encouraging the growth of entrepreneurs. Tidar University is always trying to create new entrepreneurs. However, Tidar University has not yet evaluated how much the effectiveness of entrepreneurship teaching on students' entrepreneurial readiness. Therefore, research is needed in analyzing the factors that affect entrepreneurial readiness. The research was conducted at Tidar University from March to April 2020. The population of this study was students of the Faculty of Agriculture from Semester 2 to Semester 8 in the 2019/2020 academic year. The number of samples is 120 people. Data were analyzed using descriptive statistics. The results showed that the more students get training, the more ready they are to become entrepreneurs. Students suggest the following training to complement their existing skills: a) digital marketing, b) practical work training, c) success story seminars, d) business risks, e) business basics and soft skills, f) facing global markets and innovation, g) performance management, h) entrepreneurial mentality and spirit, i) how to capture business opportunities, j) marketing, k) time management and money management, l) agrosociopreneurs, m) building networks, and n) business tips and tricks. Students with high entrepreneurial education intentions have relatively less entrepreneurial readiness. This is because they have a lot of knowledge base which encourages them to be more careful if they want to start a business. Students have the perception that entrepreneurial readiness cannot be measured by the GPA value. Entrepreneurial experience encourages students to be ready to return to entrepreneurship